2017
DOI: 10.3390/su9101779
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on Sustainable Opportunities Recognition. A Polyvinyl Chloride (PVC) Joinery Industry Analysis Using Augmented Sustainable Development Process Model

Abstract: This paper analyzes factors influencing recognition of sustainable opportunities by using an augmented sustainability process model. The conceptual model used two main factors, Knowledge and Motivation, and one moderating variable, Social embeddedness. We investigated entrepreneurs from PVC joinery industry and concluded that while market orientation and sustainable entrepreneurial orientation definitely and positively influence sustainable opportunity recognition, others variables like knowledge of the natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 156 publications
(286 reference statements)
0
10
0
Order By: Relevance
“…In one of very few empirical studies of sustainable entrepreneurship and opportunity identification, a study of the PVC industry of Romania analyzed the factors that positively influence on sustainable opportunity recognition, and found that there are knowledge-related factors, including natural/communal environment, sustainable development, market-oriented, and entrepreneurship; and motivation-related factors, including perception of threats to the natural/communal environment, altruism toward others, and success. They also found that social embeddedness is a moderator [66].…”
Section: Sustainable Opportunities and Entrepreneurshipmentioning
confidence: 97%
“…In one of very few empirical studies of sustainable entrepreneurship and opportunity identification, a study of the PVC industry of Romania analyzed the factors that positively influence on sustainable opportunity recognition, and found that there are knowledge-related factors, including natural/communal environment, sustainable development, market-oriented, and entrepreneurship; and motivation-related factors, including perception of threats to the natural/communal environment, altruism toward others, and success. They also found that social embeddedness is a moderator [66].…”
Section: Sustainable Opportunities and Entrepreneurshipmentioning
confidence: 97%
“…The respondents of the study recognized, and developed opportunities based on their salient role identities that are related to prior entrepreneurial work and personal life experiences. Knowledge and competences in particular domains are key in opportunity recognition and development and salient roles are associated with knowledge and competences of specific domains [36,95]. As highlighted earlier, social and role identities influenced scaling up of opportunities, with some respondents assuming roles that they considered key in achieving their goals.…”
Section: Discussionmentioning
confidence: 92%
“…Individuals with salient communitarian and missionary social identities and deeply entrenched developer role identity similarly attend to changes in the local natural and communal environment to come up with a business idea aimed at solving identified environmental and or social problems [95]. The idea might not necessarily lead to totally new products or services, but could lead to adaptation of already existing products, services, or practices to a completely new context.…”
Section: Opportunity Recognitionmentioning
confidence: 99%
“…Among the main articles in this field are corner article (2010) entitled "How opportunities develop in social entrepreneurship" (Corner and HO, 2010). In addition to social entrepreneurship, the second batch of papers in this cluster focus on sustainable opportunity recognition, sustainable development and macroeconomic development (Ploum et al, 2018;Filser et al, 2019;Ceptureanu et al, 2017;Belz and Binder, 2017). In total, it can be stated that…”
Section: Entrepreneurial Opportunity Recognitionmentioning
confidence: 99%